2023
DOI: 10.21608/cat.2023.327080
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Physiological and Molecular Mechanisms of Halophytes' Adaptation to High Salinity Environments: Implications for Enhancing Plant Salinity Tolerance

Randa Mohamed,
Waleed Khalil,
Mohamed Zaghloul

Abstract: Salinity stress poses a significant challenge to plant growth and agricultural productivity worldwide. However, certain plant species, known as halophytes, have evolved remarkable adaptive mechanisms to thrive in high salinity environments. Understanding the physiological and molecular mechanisms underlying the salt tolerance of halophytes holds great potential for enhancing salinity tolerance in non-halophytic crop plants. This review aims to explore the adaptive strategies employed by halophytes to cope with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Recent genetic and molecular research has revealed complicated regulatory pathways and networks through which halophytes coordinate their adaptation and tolerance to stress [12][13][14][15]. Numerous molecules are involved in these networks, with sulfur (S) being one of the key players.…”
Section: Introductionmentioning
confidence: 99%
“…Recent genetic and molecular research has revealed complicated regulatory pathways and networks through which halophytes coordinate their adaptation and tolerance to stress [12][13][14][15]. Numerous molecules are involved in these networks, with sulfur (S) being one of the key players.…”
Section: Introductionmentioning
confidence: 99%